Prevalence of malnutrition among under-five children in Al-Nohoud province Western Kordufan, Sudan - Elmanssury A. Elnadif (Intelektual Pustaka Media Utama, 2020)
Malnutrition remains one of the most common causes of childhood morbidity and mortality worldwide. The objective of this research was to determine the prevalence of malnutrition and related factors among Al-Nohoud children between 6-59 months of age. For the choice of parts, blocks and households, a three-stage sample design was used. Data collection was focused on anthropometric tests and structured questionnaires. The prevailing low weight, stunting and wasting of 16.7%, 13.5% and 17.6%, respectively, was shown. Two thirds (67%) %) of the affected children were 24 months. Female children were further underweight than male children. Home-wives achieved lower education levels and were higher in the mothers of malnourished children than those with healthy children. This study found that age of mothers, mother and family income have substantial malnutrition linked to children under the age of five (p= 000, X2= 57.40) (p= .004, X2= 41.00) (p= .00, X2= 32.74). The study found that under-five children were particularly malnutrition. Age ranges were significantly linked to wasting, stunting and underweight. Sex, mother's age, mother's level of education and family income differ greatly from malnutrition for children under the age of five.